Cross‐sectional survey of Australian and New Zealand clinical staff to explore attitudes regarding medication prescription and administration during neonatal emergencies. (21st October 2021) - Nguyen, Timothy; Illipparampil, Rosin; Wylie, Liana; Cohen, Naomi S; Clark, Megan; Bhatia, Risha; Duthie, Kate; Craig, Simon
Abstract : Aim: To survey Australasian neonatal medical and nursing staff to determine confidence regarding medication use, prior experience with medication errors and common resources utilised in neonatal emergencies. Methods: Data were collected through a cross‐sectional online survey distributed to clinical staff affiliated with the Australian and New Zealand Neonatal Network. Information collected included: demographics, confidence in medication use, medication errors and resources used to assist with medication administration. Outcomes were compared between medical staff and nursing staff, and between clinical staff with differing levels of clinical experience (<5 years, 5–10 years and >10 years). Results: Respondents ( n  = 133) were most confident in calculating medication doses (89%, n  = 119), but least confident in prescribing medication (50%, n  = 67). Nurses were more likely to be confident than doctors with respect to appropriately diluting and drawing up medication (88% nurses vs. 28% doctors, P  < 0.0001), and administering intravenous medications to critically ill neonates (97% nurses vs. 82% doctors, P  < 0.01). Over half of respondents reported being personally involved in a medication error in the last 12 months: 33% had been involved in an error related to delayed administration, 18% related to incorrect documentation and 17% related to an incorrect dose. Free‐text responses highlighted issues relating to adrenaline (epinephrine) administration and difficulties with equipment (syringe drivers and/or infusion pumps). Conclusions: Medication errors in neonatal emergencies are common. Strategies to reduce such errors should be implemented in settings where neonates may require emergency care or resuscitation.